The World Bank Group's Response to the Global Economic Crisis : Phase 1 - Independent Evaluation Group (Washington, DC: World Bank, 2012)
The global economic crisis that began in 2008 threatened to erase years of progress in developing countries. In response, the World Bank Group increased lending to unprecedented levels. The World Bank posted a large increase in middle income countries (MICs), and a much smaller one in low income countries (LICs). The International Finance Corporation (IFC) focused on trade finance, mainly in LICs. Its new business initially fell in MICs, rebounding only in late fiscal 2010. The Multilateral Investment Guarantee Agency (MIGA) concentrated on guarantees in Eastern Europe. Analytic and advisory work helped inform government and private sector responses to the crisis. This report presents an initial real-time evaluation of the readiness, relevance, quality-at-entry, short-term results, and likely sustainability of the Bank Group response from the start of the crisis through fiscal 2010. This evaluation builds on a 2008 Independent Evaluation Group (IEG) assessment of Bank Group interventions during past crises and draws extensively on 11 country case studies and field visits. Given the short time since the crisis response started, the evaluation is geared more to raising flags than to presenting definitive conclusions.